SUBSTITUTION, AUGMENTATION, MODIFICATION AND REDEFINITION (SAMR) MODEL TO TECHNOLOGY INTEGRATION FOR ENGLISH TEACHERS AT SMP NEGERI 2 SUNGGUMINASA - Intan, Nur; AM, St. Asriati; Hijrah (Journal of Computer Interaction in Education, 2024)
This study aims to determine the dominating level of substitution, augmentation, modification and redefinition (SAMR) use by the teachers in teaching English and the reasons of the English teachers use that level, namely substitution, augmentation, modification and redefinition (SAMR). This research was conducted in January 2023 from 3 English teachers at SMP Negeri 2 Sungguminasa. This research used descriptive qualitative method, and the instruments used are observation and interviews.The findings of this study indicate that of the four levels of the SAMR model, the most dominant used by English teachers is at the substitution level. And the lowest usage is redefinition. The second finding is the reason why the English teachers are at this level is due to a lack of IT-related knowledge, insufficient school facilities, and a lack of spaces that can assist teachers in improving their IT skills.